2019
DOI: 10.1016/j.lungcan.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

First-line afatinib for advanced EGFRm+ NSCLC: Analysis of long-term responders in the LUX-Lung 3, 6, and 7 trials

Abstract: In patients with advanced epidermal growth factor receptor mutation-positive (EGFRm+) non-small cell lung cancer (NSCLC), first-line afatinib significantly improved progression-free survival (PFS) and objective response vs. platinum-doublet chemotherapy in the phase III LUX-Lung 3 and LUX-Lung 6 trials, and significantly improved PFS, time to treatment failure and objective response vs. gefitinib in the phase IIb LUX-Lung 7 trial. We report post-hoc analyses of efficacy, safety and patient-reported outcomes (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…This is slightly lower than observed in clinical trials (10%-12%). 64 Overall, these extensive and robust data support the use of afatinib as a firstline treatment option against major uncommon EGFR mutations.…”
Section: Discussionmentioning
confidence: 88%
“…This is slightly lower than observed in clinical trials (10%-12%). 64 Overall, these extensive and robust data support the use of afatinib as a firstline treatment option against major uncommon EGFR mutations.…”
Section: Discussionmentioning
confidence: 88%
“…13 The frequency of Del19 mutation-positive NSCLC was slightly higher among long-term responders in the LUX-Lung 3,6,7 analysis, which supports its known role as a biomarker for improved outcomes with EGFR-TKIs vs other mutation types. 13 These studies also demonstrate that afatinib can provide clinical benefit in advanced NSCLC patients with brain metastases or uncommon mutations. 17,22,23 Although the LUX-Lung 7 trial showed that afatinib compared to gefitinib significantly improves PFS and the time-to-treatment failure, more serious drug-related adverse events were reported in the afatinib group than in the gefitinib group.…”
Section: Co-mutations and Outcomes With Egfr-tkismentioning
confidence: 60%
“…17 Overall, analysis of the LUX-Lung 7 data together with the LUX-Lung 3 and LUX-Lung 6 data show that afatinib results in approximately 10% of patients achieving long-term clinical benefit (long term response ≥3 year PFS and OS), which is greater than that observed with first-generation EGFR-TKIs. 13 Stratification factors in these trials included: Del19 versus L858R EGFR and vs. other 'uncommon' mutations in LUX-Lung 3 and LUX-Lung 6; race (Asian versus non-Asian) in LUX-Lung 3 only, and brain metastases (presence versus absence) in LUX-Lung 7 only. 13 The frequency of Del19 mutation-positive NSCLC was slightly higher among long-term responders in the LUX-Lung 3,6,7 analysis, which supports its known role as a biomarker for improved outcomes with EGFR-TKIs vs other mutation types.…”
Section: Co-mutations and Outcomes With Egfr-tkismentioning
confidence: 99%
See 2 more Smart Citations